2002
DOI: 10.1152/advan.00007.2001
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of web-based, multimedia tutorials for teaching methods of human body composition analysis

Abstract: This study examined the effectiveness of a series of Web-based, multimedia tutorials on methods of human body composition analysis. Tutorials were developed around four body composition topics: hydrodensitometry (underwater weighing), dual-energy X-ray absorptiometry, bioelectrical impedance analysis, and total body electrical conductivity. Thirty-two students enrolled in the course were randomly assigned to learn the material through either the Web-based tutorials only ("Computer"), a traditional lecture form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 1 publication
(1 reference statement)
2
31
0
2
Order By: Relevance
“…Later, studies by Buzzell et al (2002) using web-based tutorials yielded neutral findings when compared to traditional teaching methods. Borokhovski et al, (2015) in their recent meta-analysis of technology integration concluded that, "even development and introduction to educational practice of much more sophisticated computer tools and applications (what is often referred to as interactive, multi-functional, mobile, "smart" technology) have not impacted students' learning outcomes impressively enough to consider the issue unequivocally resolved in favor of proponents of educational technology (p. 1764).…”
Section: Incorporating Technology In the Classroommentioning
confidence: 99%
“…Later, studies by Buzzell et al (2002) using web-based tutorials yielded neutral findings when compared to traditional teaching methods. Borokhovski et al, (2015) in their recent meta-analysis of technology integration concluded that, "even development and introduction to educational practice of much more sophisticated computer tools and applications (what is often referred to as interactive, multi-functional, mobile, "smart" technology) have not impacted students' learning outcomes impressively enough to consider the issue unequivocally resolved in favor of proponents of educational technology (p. 1764).…”
Section: Incorporating Technology In the Classroommentioning
confidence: 99%
“…This suggests that multimedia methods have added a measure of relevance to the topic not present in the lectures. This may be due to the design of the technology, the virtual nature of interactive animations, combined with videos of actual procedures (Buzzell, Chamberlain, & Pintauro, 2002). The students felt more motivated when the technology helped them to build a practical understanding of the contents.…”
Section: The Design Of the Technology Contributes To The Students' Momentioning
confidence: 99%
“…One of the real advantages to the use of educational technology is to free time for the teachers to devote to the higher levels of cognitive learning of their students, such as synthesis, analysis, and evaluation (Buzzell et al, 2002).…”
Section: The Design Of the Technology Contributes To The Students' Momentioning
confidence: 99%
“…Le résultat d'un sondage effectué auprès des étudiants en médecine de l'ULP-Strasbourg, réalisé à l'occasion du congrès IPM 2003 3 , révélait que 44 % d'entre-eux avaient accès à Internet à domicile, 43 % bénéficiaient de cet accès à la faculté (21 postes sont disponibles à la bibliothèque de la faculté de médecine de Strasbourg par exemple), 12 % y avaient accès à partir d'autres sources et que seuls 1 % n'avaient aucun accès. Il semble que les activités d'enseignement et d'apprentissage organisées à partir de ce type de ressources numériques permettent d'offrir, lorsqu'elles sont organisées de façon rationnelle, un niveau de formation au moins équivalent aux dispositifs classiques 4,5 . La question de la nature et de la qualité des ressources didactiques attendues de la part des étudiants des facultés françaises a été évoquée conjointement au sein des groupes de travaux dirigés (TD), organisés les années précédentes avec les différentes promotions.…”
Section: Problématique Orientations Pédago-giques Conceptuelles Et Funclassified